ESTIMASI POROSITAS DAN PERMEABILITAS RETAKAN AKIBAT GEMPA BUMI TAHUN 2000 DI JALAN DANAU DENDAM BENGKULU DENGAN LATTICE GAS AUTOMATA (LGA) - Halauddin Halauddin (Inersia: Jurnal Teknik Sipil, 2019)
This research purposed to determine the total porosity (?) and permeability (k) of cracks result of the earthquake of 2000 years in the road of Dendam lake Bengkulu. Porosity and permeability calculations performed using the model Lattice Gas Automata (LGA) which implemented with Delphi 7.0 programming language. From the results of the calculation data, obtained that the cracks that have the greatest permeability obtained for cracks 3 with permeability values (k) is 10,115704 pixel 2 tot, and total porosity (?) for cracks 3 is 0,108565. While the cracks that have the smallest permeability obtained in the cracks 2 with permeability values (k) is 1.138247 pixel 2 tot, and total porosity (?tot) for cracks 2 is 0,087898. Simulation of fluid flow at the time of running data for a small porosity causing the collision of fluid flow models of LGA are becoming more frequent, there for causing the permeability is decreases. Otherwise, for a big porosity causing the collision of fluid model of LGA are becoming less frequent, there for causing the permeability is increases.